Experimentální ověření měření akcelerace a výskoků pomocí inerciálních senzorů pro sportovní aplikace - Prycl, David; Sigmund, Martin; Mráz, Lubomír; Šimek, Milan (International Society for Science and Engineering, o.s., 2018)
Článek pojednává o experimentálním ověření akcelerace z MEMS senzorů na bázi UWB. Většina dostupných systémů na trhu není schopna nabídnout detailní kinematiku mikro pohybů jednotlivých hráčů (akcelerace, výskoky) při sportovní aktivitě, za účelem vyhodnocení jejich zátěže. Systém byl vyvíjen přímo pro míčové sporty jako je futsal, házená, basketbal atp., tedy sporty, které se hrají převážně ve vnitřním prostředí.

This article deals with an experimental evaluation of measurement of acceleration using UWB-based MEMS sensors. Most of the available systems on the market unable to provide a detailed kinematics of of individual player’s the micro-movements (acceleration, jump) during sportive activity in direction of their load evaluation. The proposed system was developed directly for ball sports such as football, handball, basketball, etc., i.e. sports that are mainly played in the indoor environment.
Experimental evaluation of measurement of acceleration and jumps using inertial sensors for sport applications